Achene dimorphism in Bidens pilosa L. (Asteraceae) as determined by germination test - Amaral, A.; Takaki, M. (Inst Tecnologia Parana, 1998)
The germination of achenes of Bidens pilosa L. was analyzed during the life span of the mother plant. Decrease in the range of achene size was monitored until the senescence of the mother plant when the shortest achenes were harvested. The analysis of the germination percentage confirmed the presence of two distinct classes, formerly defined as shea and long ones. Because length can not be used for the separation of those classes, the morphological characteristics of the tegument, specially of the ornament must be used for separation of the achenes with verrucose tegument (formerly named as short achenes) and achenes without ornament of the tegument (formerly named as long achenes). The achenes with verrucose tegument presented dormancy and light sensitivity, and the achenes without ornament of the tegument presented no dormancy and no light sensitivity for the germination process.
Keywords: Bidens pilosa; seed dimorphism; phytochrome; seed germination